Contemporary women's health : - Kolander, Cheryl A. (McGraw-Hill/Irwin, 2004)
This text provides a balanced, comprehensive understanding of the health issues affecting women. Health information is presented within the context of the social and political forces affecting women of all ages, races, and ethnicities. Text highlights include detailed information on prevention and consumer choice, as well as coverage of the impact of lifestyle issues and relationships on women’s health throughout the lifespan.